A three‐field stabilized finite element method for fluid‐structure interaction: elastic solid and rigid body limit. (1st July 2015) - Hachem, E.; Feghali, S.; Coupez, T.; Codina, R.; Dolbow, John; Farhat, Charbel; Harari, Isaac; Lew, Adrian
Summary We propose a full Eulerian framework for solving fluid‐structure interaction (FSI) problems based on a unified formulation in which the FSIs are modelled by introducing an extra stress in the momentum equation. The obtained three‐field velocity, pressure and stress system is solved using a stabilized finite element method. The key feature of this unified formulation is the ability to describe different kind of interactions between the fluid and the structure, which can be either elastic or a perfect rigid body, without the need of treating this last case via penalization. The level‐set method combined with a dynamic anisotropic mesh adaptation is used to track the fluid‐solid interface. Copyright © 2015 John Wiley & Sons, Ltd.